Effect of asbestos exposure on differentiation and function of cytotoxic T lymphocytes - Kumagai-Takei, Naoko (Environ Health Prev Med, 2020)
Asbestos exposure is known to cause malignant mesothelioma, which is associated with poor prognosis. We focused on and examined the effect of asbestos exposure on the differentiation and function of cytotoxic T lymphocytes (CTLs). CTLs have the ability to specifically attack tumor cells after being differentiated from naïve CD8(+) T cells following antigen stimulation. Exposure to chrysotile B asbestos suppressed the differentiation of CTLs during the mixed lymphocyte reaction (MLR) and was associated with a decrease in proliferation of CD8(+) T cells. Additionally, in an effort to investigate the mechanism associated with suppressed CTL differentiation upon exposure to asbestos, we focused on IL-2, a cytokine involved in T cell proliferation. Our findings indicated that insufficient levels of IL-2 are not the main cause for the suppressed induction of CTLs by asbestos exposure, although they suggest potential improvement in the suppressed CTL function. Furthermore, the functional properties of peripheral blood CD8(+) lymphocytes from asbestos-exposed individuals with pleural plaque (PP) and patients with malignant mesothelioma (MM) were examined. MM patients showed lower perforin levels in CD8(+) lymphocytes following stimulation compared with PP-positive individuals. The production capacity of IFN-γ in the MM group tended to be lower compared with healthy volunteers or PP-positive individuals. In an effort to determine whether chronic and direct asbestos exposure affected the function of CD8(+) T cells, cultured human CD8(+) T cells were employed as an in vitro model and subjected to long-term exposure to chrysotile (CH) asbestos. This resulted in decreased levels of intracellular perforin and secreted IFN-γ. Those findings underlie the possibility that impaired CD8(+) lymphocyte function is caused by asbestos exposure, which fail to suppress the development of MM. Our studies therefore reveal novel effects of asbestos exposure on CTLs, which might contribute towards the development and implementation of an effective strategy for the prevention and cure of malignant mesothelioma.